Age-specific neonatal mortality and associated factors in the 2021 state of Rio de Janeiro (Brazil) birth cohort - Pauline Lorena Kale; Sandra Costa Fonseca (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT Objective: To analyze the causes of age-specific neonatal deaths and death-associated factors in the 2021 state of Rio de Janeiro birth cohort. Methods: Retrospective cohort of live births (LB) followed up to 27 days of delivery (<24hs, 1-6 and 7-27 days). Data obtained from the Information Systems on Live Births (2021) and Mortality (2021/2022). We described the distributions of maternal and newborn characteristics and causes of death. We used multinomial regression models with hierarchical levels of determination of neonatal death. Results: Of the 179,837 LB, 274 died within 24 hours, 447 within 1-6 days and 324 within 7-27 days. The neonatal mortality rate was 5.8‰ LB (CI 95%: 5.5-6.2). Neonatal survivors and deaths were heterogeneous according to the analyzed characteristics, except for the reproductive history (p<0,05). 78% of causes of death were avoidable. Causes reducible by adequate care for pregnant women (<24 hours and 1-6 days) and newborns (7-27 days) predominated. Low schooling showed a significant association for deaths between 7-27 days (ORajusted=1.3); mixed race, for deaths between 1-6 days (ORajusted=1.3), and black color for both age groups (1-6 days: ORajusted=1.5 and 7-27 days: ORajusted=1.8). Health care and biological factors of LB (intermediate and proximal levels) remained strongly associated with neonatal death, regardless of age. Conclusion: Causes of death, factors associated with neonatal death, and strength of association differed according to death-specific age. Preventive actions for neonatal death should consider sociodemographic vulnerabilities and intensify adequate prenatal and perinatal care.